Molecular dynamics simulations and experimental studies on low-temperature growth of GaN - Xiang Li; Yi Luo; Lai Wang; Jian Wang; Zhibiao Hao; Changzheng Sun; Yanjun Han; Bing Xiong; Hongtao Li (Materials Research Express, 2024)
Growth mechanisms of (0001) wurtzite GaN films at low temperature are investigated by molecular dynamics simulations and experiments. The crystallization properties of GaN films deteriorate dramatically at low temperature due to the limited energy available for atomic surface migration and incorporation into the perfect lattice sites. In our simulation, growth interruption stage is periodically introduced and the as-deposited GaN films are treated with energy-carrying argon ions at this stage. The surface atoms located at the weak binding sites can acquire energy from the argon ions for secondary migration and incorporation into the perfect lattice sites. As a result, the crystallization properties of GaN films are significantly improved. GaN films are experimentally grown on sputtered AlN/sapphire substrates at 600 °C via inductively coupled plasma metal organic chemical vapor deposition along with periodic argon plasma treatment. The as-deposited film acquires energy from the plasma, leading to significant improvement of the crystalline properties. The surface morphology of the GaN film demonstrates a noticeable smoothing effect, with an evident increase in grain size from submicron to micron level. Additionally, GaN film with the optimized surface morphology exhibits high c -axis and in-plane orientations, and the full width half maximums of (002) and (102) x-ray diffraction rocking curves are 0.25° and 0.32°, respectively. These results provide effective guidance for the growth of GaN films at low temperature.